Estimation of Ecotoxicity of Nanoparticles of Cobalt, Copper, Nickel and Zinc Oxides on Biological Indicators of the State of Ordinary Chernozem - S. I. Kolesnikov; V. M. Varduni; A. N. Timoshenko; T. V. Denisova; K. Sh. Kazeev; Yu. V. Akimenko (Юг России: экология, развитие)
Aim. Assessment of the effect of nanoparticles of oxides of cobalt, nickel, copper, zinc on the biological state of ordinary chernozem.Material and Methods. The effect of Co3O4, CuO, NiO and ZnO nanoparticles on the biological properties of soil was studied on ordinary chernozem (Rostov‐on‐Don, ussia). We studied the effect of various concentrations of pollutants depending on their content in soil of 3, 10, 30 backgrounds. Co3O4, CuO, NiO and ZnO nanoparticles with a size of <50 nm and TiO2 of <100 nm.Results. Contamination of ordinary chernozem by Co3O4, CuO, NiO and ZnO and their nanoparticles leads to a deterioration in its biological properties in terms of: total bacteria numbers; abundance of bacteria of the genus Azotobacter; activity of catalase; activity of dehydrogenases and decrease in seed germination and length of radish roots. The oxides of the elements under study had an approximately equal negative effect on these indicators, while among the nanopowders the most toxic were the oxides of copper and zinc and the least was cobalt oxide. It was established that the nanopowders of Co3O4, CuO, NiO, and ZnO reduce the biological indices of ordinary chernozem to a greater extent than the ‘conventional’ forms of oxides. A stimulating effect of the studied substances on the biological properties of ordinary chernozem was not recorded. This indicates a high toxicity of the studied substances, which is also characteristic of nanoparticles of other elements.Conclusion. Contamination by nanoparticles of oxides of cobalt, nickel, copper and zinc has a negative effect on the biological state of chernozem and is more pronounced than contamination by ‘conventional’ forms of these oxides.